Measuring skill in rugby union and rugby league as part of the standard team testing battery - Hendricks, S.; Lambert, M.; Masimla, H.; Durandt, J.; Gabbett, T. (International Journal of Sports Science and Coaching, 2015)
Coaches, strength and conditioning coaches, and researchers typically use a standard testing battery as a screening tool to measure physical characteristics of players. The information from this testing battery is subsequently utilized to check whether a player can meet the demands of the sport, talent identification, long-term player development, squad/team selection and/or for designing training programs. Apart from these physical attributes, Rugby players (both Union and League) also need to efficiently execute a range of technical and tactical skills during a match. Attempts to assess skill in Rugby have been reported, but little has been documented on assessing skill as part of a Rugby team testing battery. This review highlights the use of, and requirements of, a skill assessment that can be used in a Rugby team setting. When devising a skill assessment, a number of factors such as standardisation, validity, reliability, logistics, player safety, ecological validity, and representative design need to be considered. All these factors should be considered on a continuum, and not in absolute terms. The 1 vs 1 attacker and defender interactions allow for an acceptable degree of ecological validity and representative design, and logistically seems most appealing for team testing. Also, using a valid and reliable set of technical criteria and outcome measures has shown to be most appropriate to standardise a skill assessment. ABSTRACT FROM AUTHOR